If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -2n = 6 Solving 20 + -2n = 6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -2n = 6 + -20 Combine like terms: 20 + -20 = 0 0 + -2n = 6 + -20 -2n = 6 + -20 Combine like terms: 6 + -20 = -14 -2n = -14 Divide each side by '-2'. n = 7 Simplifying n = 7
| 0.916*8.2= | | 4n+4=16n | | 10n=20-10n | | 3n=n+63 | | a*a*a*a*a= | | 4x+6.2=0.4-x | | 70.5-70.36= | | 3x+42=6-6 | | 3(x+4)-8=7 | | 11n=2n+27 | | -5x+13x=18 | | 10n-8=102 | | 3n-7=21 | | 6*z+5=15 | | 12x=-2x+10x | | 6-4(a)=15 | | 2x+7=73-8x | | 4(a+2)-9(a+9)=-4(2a+9)-16 | | -8+9+(-4)+6= | | x^3=-31 | | 5.6-0.221= | | 2*a-5=12 | | 8.4-(-6.5)= | | 24-5*a=15 | | y+1=30 | | (2x)2+x=3 | | 7x-1+117=180 | | 69-4x=14x+19 | | 7p-14=-17+4p | | 2t-18=-11+t | | 3(x-4)2-8=4 | | 2a-7=2(a+1)+9a+1 |